High energy electron irradiation effects on polystyrene films - Mathad, R. D.; Kumar, H. G. Harish; Sannakki, B.; Ganesh, S.; Sarma, K. S. S.; Badiger, Manohar V. (Radiation Effects and Defects in Solids, 2009)
The effect of an 8MeV electron-beam on the structural, optical and dielectric properties of polystyrene films has been investigated respectively by means of Fourier transform infrared (FTIR) spectroscopy, ultraviolet-visible (UV-VIS) spectroscopy and electrical impedance (LCR) analysis over a radiation dose in the range of 50-250kGy using a Microtron accelerator. The FTIR spectral analysis shows no change in the overall structure of the irradiated polystyrene films, except a minor change in the intensity of a few peaks in the FTIR spectrum, indicating that polystyrene is resistant to electron-beam irradiation over the range of radiation doses investigated. The optical band gap analysis using the UV-VIS absorption spectra of the polystyrene shows a small decrease in the optical band gap (Eg) and the activation energy with an increase in electron doses. Further, the dielectric measurements over a frequency range of 100Hz to 1MHz for the electron-beam-irradiated polystyrene films show that both the dielectric constant and the dielectric loss increase with an increase in electron radiation dose, which may be ascribed to the formation of defect sites in the band gap of polystyrene as a consequence of molecular chain scission in the polymer films upon irradiation.
Keywords: electrons; optical spectroscopy; Polymers; radiation